2022
DOI: 10.3390/horticulturae9010024
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Fruit Quality in Astringent and Non−Astringent Persimmon Fruit Germplasm

Abstract: Persimmon (Diospyros kaki Thunb.) is an economically important tree with a long history of cultivation in China. So far, a total of approximately 1000 varieties have been found in China. To systematically evaluate the diversity of persimmon fruit quality, 22 quality measures of appearance, intrinsic, and sensory quality were evaluated using 61 typical persimmon fruit. According to the findings, the coefficient of variation (CV) of 15 appearance and intrinsic quality index values ranged from 13.81% (fruit shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…In this study, 56 fruit phenotypic traits from 150 persimmon germplasm resources with consistent establishment and cultivation management conditions were comprehensively analyzed. Previous studies have revealed a wide range of variation (ranging from 11.06% to 50.88%) in persimmon fruit traits, and our results also show coefficients of variation in phenotypes ranging from 5.10% to 56.78% [17,24,25]. The large coefficients of variation indicate a large diversity of phenotypic traits in persimmon germplasms, which can provide rich test materials for genetic improvement and variety selection.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…In this study, 56 fruit phenotypic traits from 150 persimmon germplasm resources with consistent establishment and cultivation management conditions were comprehensively analyzed. Previous studies have revealed a wide range of variation (ranging from 11.06% to 50.88%) in persimmon fruit traits, and our results also show coefficients of variation in phenotypes ranging from 5.10% to 56.78% [17,24,25]. The large coefficients of variation indicate a large diversity of phenotypic traits in persimmon germplasms, which can provide rich test materials for genetic improvement and variety selection.…”
Section: Discussionsupporting
confidence: 74%
“…One of the most critical aspects that determines a fruit's economic value and has a direct impact on its ability to compete in the market is the fruit's quality [39]. Both the intrinsic qualities and the appearance of the fruit are considered to be part of the fruit's quality [17]. Color, shape, and size are the appearance qualities of the fruit that are important indices for evaluating the quality of commodities and the characteristics of varieties, and they serve as a basis for satisfying consumers' demands for a "good look"; fruit hardness and water content are internal qualities, which impact customers' purchasing decisions [17,40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations